A comparative study of the radial pulse between primary dysmenorrhea patients and healthy subjects during the menstrual phase - Kim, Jihye (Sci Rep, 2019)
The aim of this study was to compare radial pulse characteristics between primary dysmenorrhea (PD) patients and healthy subjects throughout the menstrual cycle. A total of 48 females aged 20 to 29 years participated, and all subjects were assigned to two groups according to their visual analogue scale scores. The radial pulse of each subject was obtained using a pulse tonometric device during menstrual, follicular, and luteal phases. In addition, various pulse analysis indices were used to estimate the pulse characteristics. The pulse tension index (PTI) and pulse depth index (PDI) in the patient group were significantly lower than those in the healthy group during the menstrual phase (P < 0.01 and <0.001, respectively). According to univariate logistic regression results, the PTI, PDI and optimal applied pressure (OAP) were significantly correlated with PD, and the model based on the PTI and OAP performed best (AUC = 0.828). This study is the first to analyze pulse tension inferred from the PTI and to apply this parameter to clinical practice. The results of this study confirmed the possibility of quantitatively measuring pulse tension and suggest that the PTI and OAP can serve as potential clinical indicators for pain disorders.